Power and Organization Life Cycles - Mintzberg, Henry (Academy of Management Review, 1984)
Zusammenfassung From the earliest days of organization theory, notably in the writings of Max Weber1, the themes of ideal or pure types of organizations and of stages of organizational development have occupied an important, although never prevalent, place in the literature. The recent book by Kimberly and Miles (1980) entitled The Organizational Life Cycle may signal a growing interest in these themes or may, in fact, stimulate such an interest.